GREEN ACCOUNTING, SUSTAINABILITY REPORTS AND DEBT POLICY ON FINANCIAL PERFORMANCE - Sefi Aulia Nur Asifah ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
The decline in financial performance experienced by several companies in the raw materials sector in Indonesia following the COVID-19 pandemic has become a significant concern amid economic uncertainty, fluctuations in raw material prices, and supply chain disruptions. This situation requires companies to optimize asset management and operational efficiency to maintain profitability and competitiveness in an increasingly competitive market. This study examines the effect of implementing green accounting, preparing sustainability reports, and debt policies on the financial performance of companies in the raw material sector listed on the Indonesia Stock Exchange (IDX). The purpose of this study is to analyze the implementation of green accounting, sustainability reports, and debt policies on financial performance. The research method employed is a quantitative methodology, analyzing data from 24 companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period, selected through purposive sampling. Data analysis was performed using SPSS Statistics with multiple linear regression analysis techniques. The findings suggest that green accounting and sustainability reports have a positive and significant impact on financial performance, whereas debt policy does not have a substantial effect on financial performance. These findings confirm that companies must prioritize environmental management and sustainability reporting to enhance profitability. Although debt policy is essential, its impact on return on assets (ROA) is not directly apparent. By focusing on green accounting and sustainability reports, companies can enhance their financial performance sustainably.